Voting Rights for Whom? Examining the Effects of the Voting Rights Act on Latino Political Incorporation. Issue 3 (7th May 2015) - Marschall, Melissa J.; Rutherford, Amanda
Abstract : This study applies insights from principal‐agent models to examine whether and how the language assistance provisions of the Voting Rights Act, Sections 203 and 4(f)(4), affect Latino representation. Using panel data from 1984–2012, we estimate two‐stage models that consider the likelihood and extent of Latino board representation for a sample of 1, 661 school districts. In addition, we examine how policy design as well as federal oversight and enforcement shape implementation and compliance with the language assistance provisions. Our findings not only provide the first systemic evidence that the language assistance provisions have a direct effect on Latino representation, but also link the efficacy of the language assistance provisions to the duration and consistency of coverage and the presence of federal elections observers. Overall, our study underscores the continued need for federal government involvement in protecting the voting rights of underrepresented groups, in this case, language minority citizens.